Particle-based nutrients and metal contaminants in the habitat of Unionidae mussels in the Tisza River (Hungary) - Dobosy, Péter; Almeshal, Wael; Illés, Ádám; Tserendorj, Davaakhuu; Sandil, Sirat; Kovács, Zsófia; Endrédi, Anett; Záray, Gyula (Frontiers in Environmental Science, 2023)
Unionidae is a species-rich family of freshwater mussels with an almost worldwide distribution. In Central European rivers, Unio crassus, Unio tumidus, and Unio pictorum have relatively high populations. In order to characterize the habitats of these suspension feeders, their nutrient supply and potential metal contaminants were investigated at four sampling locations along the Tisza River. The chemical and physical properties of near-bottom suspended sediment (NBS) and bottom sediments (BS) were determined. The NBS sediments contained smaller grains than the bottom sediments, with roughly 85-90% of the particles being less than 60 µm, allowing these mussels to catch them. Contrarily, only 2.47-51.8% of bottom sediments were less than 60 µm. The NBS sediments contained 30, 23, and 15% more organic carbon, nitrogen, and phosphorous, respectively, than the bottom sediments. The rounded C:N:P molar ratios in the NBS sediments were 60:4:1, whereas they were 45:3:1 in the bottom sediments indicating that soil-derived organic materials are the main sources of the nutrient elements. The concentrations of metals were also greater in the suspended sediments, with the exception of Zn at Tokaj and Fe, Al, Mn, and Cr at Szeged. The observed metal concentrations at Tokaj and Szeged are most likely the result of prior contamination transported by the tributaries Bodrog and Maros Rivers, respectively, and stored in the top 10 cm of bottom sediments. The metal and arsenic concentrations were mostly within the range of the threshold and probable effect values; however, the mercury concentration in all sediments exceeded the probable effect concentration.